ACCESS AND USE OF ICT IN SCHOOL MANAGEMENT IN MINDANAO STATE UNIVERSITY MAIN CAMPUS - Macasawang, Jehanie May Ader (International Journal of Educational Management and Innovation, 2020)
In the digital era, the ability of schools to access and provide ICT resources is very important. This study examines the level of accessibility and use of ICT resources in school management in Mindanao State University's main campus (MSU MC). It aims to give a picture of the current profile of the ICT facilities in the university particularly those employed for school management through describing the accessibility of those ICT facilities by taking into account their availability and convenience of access and its use by pertaining to the ICT user-ability of the human resource of the university. This study was incited due to the visible difficulties met by the students as well as the teacher and staff in the school management activities in MSU MC despite the application of ICT in it. The data for this study were collected through a semi-structured survey, interviews, and document reviews of related literature. Correlation of the variables was tested using the chi-square test. And the comparative analysis of the opinions of the groups of respondents was done through a t-test. The results of this study find that over-all, the current ICT facility of the university is claimed as fairly effective in school management that only Plagiarism is seen as the most prevalent negative consequence on its implementation. In addition, the correlation analysis in this study discloses that ICT accessibility and user-ability have no direct relationship with effective school management. And although the comparative analysis showed that there is a significant difference of opinions between the groups of respondents, its statistical value proved only that the variance of the opinions of the groups of respondents is only little. These results evidently reflect that the ICT facility in MSU MC is not so much defective. However, the research results also reveal that the problems in the availability and convenience of ICT tools in MSU MC as well as in the user-ability of the human resource in ICT are pretty much important aspects of an excellent ICT facility like strong internet bandwidth, need of maintenance and update on latest ICT trends, motivation to use ICT tools, etc. Thus, this study recommends that the ICT resources in MSU MC for school management should be further developed as seen appropriate